Ekuitas Merek Produk Cap Kaki Tiga: Pengujian Model Consumer-Based Brand Equity - Joko Pramono (Universitas Tarumanagara, 2019)
This study examines consumer-based brand equity of Cap Kaki Tiga-label branding and relative signiﬁcance of brand awareness, perceived quality, and brand association on brand loyalty. As additional, this study aims to test the role of brand loyalty as a mediator on the relationship of its predictors on brand equity. A survey instrument was developed, scale measures were pretested, and the ﬁnal survey was administered directly to 210 respondents. Based on Aaker’s conceptual framework, a structural equation model (SEM) was designed to analyse the proposed relationships. A causal order between brand equity dimensions was established. The results suggest that the positive effects of brand awareness, perceived quality and brand association on brand loyalty, and overall brand equity are mediated by brand loyalty. Marketing managers should focus on brand loyalty in order to increase overall brand equity, and should give special attention to brand awareness, since it is the factor with the strongest impact on brand loyalty.